The microbiota-gut-brain axis in depression: unraveling the relationships and therapeutic opportunities - Zhu, Zhangcheng; Cheng, Yiwen; Liu, Xia; Xu, Xiaocui; Ding, Wenwen; Ling, Zongxin; Liu, Jiaming; Cai, Guangyong (Frontiers in Immunology, 2025)
Depression, a highly prevalent and relapsing mental disorder, exacts profound personal and socioeconomic tolls globally, warranting urgent scientific and clinical attention. Emerging evidence from both preclinical models and human clinical investigations has established the microbiota-gut-brain axis (MGBA) as a critical determinant in depression pathogenesis. This intricate bidirectional network integrates gut microbiota with central nervous system function, influencing mental health through mechanisms previously underrecognized. This review systematically synthesizes gut microbiota alterations associated with depression and their impacts on neuroendocrine, neuroimmune, and metabolic pathways. Advanced therapeutic strategies targeting the MGBA are discussed, including probiotics, fecal microbiota transplantation, and artificial intelligence-enabled microbiome interventions for depression management. While challenges in standardization, mechanistic understanding, efficacy and safety remain, MGBA-centered approaches offer a promising shift toward microbiota-based diagnostics and personalized treatments for depression.